Learning disabilities and retardation mental: a case study - Schoen-Ferreira, Teresa Helena (2010)
The early diagnosis is always a strong allied in the therapy of any pathology, including cases of mental retard. This way, a more appropriate and effective intervention can be planned, favouring the individual’s inclusion on the society. The objective of this study is to observe cases of learning difficulties as a manifestation of mental retard in two twin siblings 5 years, 7 months old, coursing the Stage II (grade that precedes the fundamental education in two years) of a public school of São Paulo, Brazil. In order to conduct this study, development tests in several areas and intelligence tests were applied in the children, and interviews were conducted with their mother and teachers. This way, we got information about the motor, psychological and social development of the siblings, making it possible to accompany these cases closer to the ideal way.